Implementasi Perhitungan dan Pembagian Komisi Live Tiktok dengan Metode Rowan Plan dan Emerson Plan pada Toko Diva Collection Desa Sumberejo Banyuputih Situbondo - Roni Yanto; Jamilatul Jannah (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2026)
Commission is a form of additional compensation provided by companies or MSMEs to employees as motivation for additional work performed, especially in the context of sales or promotions. Unlike a predetermined base salary, commissions are variable and depend on performance. Therefore, companies need to calculate commissions accurately in accordance with relevant accounting theory. This study aims to analyze field facts related to the calculation and distribution of commissions, as well as the commission calculation method based on cost accounting theory. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using interactive methods that include data collection, data reduction, and data presentation. The results show that commission calclations in the field differ from cost accounting theory, causing the Diva Collection store to experience obstacles in calculating commissions and salaries for employees, especially for live TikTok hosts. Both methods, namely the Rowan Plan formula and the Emerson Plan, as methods for calculating wages based on working hours and the number of products sold, have proven effective in determining fair commissions and increasing employee productivity and company efficiency.